x thuộc B ( - 10 ) = { \(0;\pm10;\pm20\);... } mà - 20 \(\le x\le20\)
=> x thuộc { \(0;\pm10;\pm20\)}
Vậy B = { - 20 ; - 10 ; 0 ; 10 ; 20 }
Vì x thuộc B(10) => x chia hết cho 10
Mà x thuộc Z và -20< x<20 => x thuộc {-20; -10; 0; 10; 20}
B={x thuộc Z/x bội của -10 và -20< x<20}
X B ( - 10 ) = { 0; ± 10; ± 20;... }
mà - 20 ≤ x ≤ 20
=> x { 0; ± 10; ± 20}
Vậy B { - 20 ; - 10 ; 0 ; 10 ; 20 }
B=(x thuộc Z/x bội của -10 và -20< x<20)
X B (- 10 ) = ( 0; + 10; + 20;... )
mà - 20 < x < 20
=> x ( 0; + 10; + 20)
Vậy B (- 20 ; - 10 ; 0 ; 10 ; 20 )